PERLINDUNGAN HUKUM TERHADAP PEREMPUAN DAN ANAK DALAM KASUS PERDAGANGAN ORANG STUDI PUTUSAN PENGADILAN NEGERI BALE BANDUNG - Leni Anggraeni, Leni Anggraeni (Jurnal Media Justitia Nusantara, 2025)
Human traffickings a modern form of slavery, occurring both at thenternational andnternational levels. With the development ofnformation technology, communication and transformation, the criminal modes of human trafficking are becomingncreasingly sophisticated. The form of legal protection against victims of human traffickings to protect the rights of every person whos a victim of the crime of human trafficking to be subject to the same treatment and protection as provided by law and law. The problem of human traffickings very complex, so efforts to prevent and overcome victims of trafficking must be carried outn anntegrated manner. There are several factors that encourage the occurrence of human trafficking,ncluding poverty, lack of awareness of looking for work without knowing the dangers of trafficking and methods used to cheat or entrap victims, culture, weak registration/documentation of births of children or residents, weak elements. -person Law enforcement officials and related parties carry out supervision overndications of criminal cases, apart from that, corruptions also one of the factorsn which human trafficking occurs. The method usedn this researchs annformative legal approach, namely a methodnnformative legal research using primary sources, secondary data or library materials. Juridical criminological analysis of traffickingn women and children can be carried out through anllegal system approach (legal system), namely through court decisions. The application of the law carried out by the judgen the court decision,n this case the decision of the Bandung Bandung State Court Number: Number 404/Pid.Sus/2022/PN Blb against the perpetrator of the criminal act of traffickingn women and children